HUBUNGAN SIBLING RIVALRY TERHADAP MOTIVASI BERPRESTASI PESERTA DIDIK SMP NEGERI 2 KOTO BARU - Qonita, Qonita; Kardo, Rici; Wae, Rahmawati (STKIP Pesisir Selatan, 2025)
This study aims to examine the relationship between sibling rivalry and achievement motivation among students at SMPN 2 Koto Baru. The research is motivated by the observation of problematic behaviors such as verbal and non-verbal aggression toward siblings, failure to complete assignments, absenteeism, and tardiness in class. A quantitative descriptive approach with a correlational method was used in this study. The population consisted of 30 students, all of whom were selected through purposive sampling. Data were collected using a questionnaire and analyzed using the product moment correlation technique to assess the relationship between variables. The findings indicate that the level of sibling rivalry among students is categorized as low, as is their level of achievement motivation. The correlation analysis revealed a very weak relationship between sibling rivalry and achievement motivation. The novelty of this research lies in its focus on the local context and the exploration of sibling rivalry as a factor influencing academic motivation at the junior high school level—an area that remains underexplored in quantitative studies. These results offer valuable insight for school counselors to design targeted interventions that promote a growth mindset and social skills development, thereby supporting students' academic motivation and overall well-being.